Identifikasi Cacing Nematoda pada Sekum dan Kolon Sapi Kurban yang Dipotong saat Idul Adha 1439 H di Wilayah Surabaya Timur - Jihaan Haajidah; Moh Sukmanadi; Kusnoto Kusnoto; Endang Suprihati; Lianny Nangoi; Poedji Hastutiek (Universitas Airlangga, 2020)
The aim of this research was to detect the presence of nematode worms that infects sacrificial cattle slaughtered duringEid al-Adha 1439 H in East Surabaya. This research used 24 sampels of sacrificial cattle and used digestive tract surgical method. Based on the result of the examination using a microscope with 100x magnification, there are positive samples infected with nematode worms. In caecum cattle consist of Oesophagostomum radiatum and Trichuris spp. In colon cattle consist of Oesophagostomum radiatum.